Models of traps for the coconut pests Rhyncophorus bilineatus and Scapanes australis and their trapping efficiency in Papua New Guinea - Titus Kakul; S. Laup; R. N. B. Prior; Didier Rochat; Jean Paul Morin; P. Gende; S. Embupa; L. Ollivier (International Coconut Community, 2004)
The beetle pests Scapanes australis, Oryctes rhinocerous and Rhyncophorus bilineatus have been major constraints to coconut production in the Islands region of Papua New Guinea for the last 30 years. Efficient synthetic attractants able to lure and trap all three beetles have been developed. This paper describes several trap designs developed at the Cocoa and Coconut Research Institute and the results obtained for their trapping efficiency in the laboratory and the field. A modification of the “Titus Bucket” trap increased the number of R. bilineatus caught threefold and of female Scapanes twofold. PVC pipe traps caught more Scapanes than the modified “Titus Bucket” trap.